Hubungan Pola Konsumsi Fe Dengan Kejadian Anemia Pada Ibu Hamil Di Desa Dasan Geria Kecamatan Lingsar Kabupaten Lombok Barat - Luchan Syella Samudra; Irianto Irianto; Reni Sofiyatin (Poltekkes Kemenkes Mataram, 2016)
Background: Based on the prevalence of anemia in Indonesia is still quite high, at 26.50% are young women, women of childbearing age (WUS) 26.90%, 40.10% of pregnant women and children under five at 47.00%. The results of the annual report Sigerongan Health Center of West Lombok in 2010 in the village of Dasan Geria anemia reached 17.17% and the increase in 2012 is 26.19%. Anemia in pregnant women will lead to high maternal mortality rate (MMR). Anemia in pregnant women can occur because one of the factors that Fe consumption patterns during pregnancy.Objective: To identify the relationship fe consumption patterns with the incidence of anemia in pregnant women in the village of Dasan Geria Lingsar District of West Lombok. Methods: This study was an observational analytic cross sectional study in terms of time, the samples were used as many as 56 pregnant women. To determine the consumption pattern of Fe with the incidence of anemia in pregnant women conducted bivariate analysis using Chi Square test with a confidence level of 5% (α 0.05). Results: Of the 56 samples based on the occurrence of gestational age the majority (82.14%) aged 2035 years, most of the work rate (64.29%) do not work, the level of education the majority (41.07%) Junior High School (SMP). Based on the results of statistical tests is known that there is no association between the consumption patterns of fe with anemia in pregnant women (p = 0.244: p> 0.05). Conclusion: There is no relationship between consumption patterns fe with anemia in pregnant women.